Frost Heave of Irrigation Canals in Seasonal Frozen Regions. (14th January 2019) - Xu, Jian; Wang, Qinze; Ding, Jiulong; Li, Yanfeng; Wang, Songhe; Yang, Yugui
Abstract : Soil frost heave acts as a driver of the emerged fracture in the concrete lining of irrigation canals and subsequent water leakage in seasonal frozen ground. A model test was carried out on the frost heave of a U-shaped canal with concrete lining. The heat and water migration during freezing, and frost heave-induced deformation, and force in normal direction were live monitored by high-precision transducers. The results prove that the freezing front descends downward over time at a specified thermal boundary, with considerable migration of water within the scope of 0–40 cm. The maximum deformation occurred at the bottom of the lining and decreased upward with the rate of frost heave lowering over time while the normal force showing little change in the monitoring points, implying that stress concentration does not show up during freezing. Besides, the layered settlement observation reveals that frost heave dominates the total deformation while creep, the universal source of deformation, accounts for a negligible proportion. A practical model was proposed based on a simple theoretical model for heat-water coupled transfer in a partially saturated medium and was numerically implemented in COMSOL. The computed results were compared with the monitored data including frozen depth, water content, normal displacement, and frost heave force. Finally, the rational thickness of the insulation board was determined based on the partial insulation method.